The Influence of Work Stress and Work Discipline on Employee Performance Mediated by Work Motivation - Rima Yulianti; Shelfi Malinda; Muhammad Ichsan Hadjri (FEBI IAIN Langsa, 2026)
This study aims to analyze the influence of work stress and work discipline on employee performance, with work motivation serving as an intervening variable, at the South Sumatra Province Trade Office. The study is motivated by inconsistencies in previous research findings regarding the impact of work stress and work discipline on employee performance, as well as the importance of examining the role of work motivation as a mediating variable. A quantitative approach with an explanatory method was employed. The study population consisted of 135 employees, all of whom were included in the sample using a saturated sampling technique. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the aid of SmartPLS 4. The results indicate that work stress does not have a significant effect on employee performance but has a significant negative effect on work motivation. Work discipline has a significant positive effect on both work motivation and employee performance. Work motivation also has a significant positive effect on employee performance. Furthermore, work motivation was found to negatively mediate the relationship between work stress and employee performance and positively mediate the relationship between work discipline and employee performance. The findings confirm that enhancing work discipline and effectively managing work stress can boost work motivation, thereby leading to improved employee performance. This study contributes theoretically to the development of organizational behavior research and offers practical implications for government agencies in designing human resource management policies aimed at enhancing employee motivation and performance.